Behaviour of Listeria monocytogenes in artisanal raw milk Pecorino Umbro cheese: a microbiological challenge test - Roberta Ortenzi; Raffaella Branciari; Sara Primavilla; David Ranucci; Andrea Valiani (Italian Journal of Food Safety, 2015)
In the present study, a microbiological challenge test in artificially contaminated raw milk Pecorino Umbro cheese during cheese-making was carried out. Raw ewe milk was contaminated by a suspension of particular Listeria monocytogenes strains. The number of L. monocytogenes and L. monocytogenes dynamic growth were evaluated during cheese-making and storage. A significant decrease of the viable count of L. monocytogenes was observed during ripening and L. monocytogenes viable count was below the limit of quantification during storage. The results show that the product is unable to support the growth of the pathogen.